Coach perspectives on coach-athlete relationships and characteristics of Generation Z academy level rugby union players from South Africa - Marc Landman; Heinrich Grobbelaar; Wilbur Kraak; Wilbur Kraak (Frontiers Media S.A., 2024)
IntroductionThe coach-athlete relationship is not merely a by-product of the coaching process but serves as its foundation. Coaches today must align their approaches with the characteristics (character, strengths, and growth areas) of a new generation of athletes, commonly referred to as Generation Z (Gen Z). Born between 1995 and 2012, Gen Z's grew up in a digital age, which shaped their character and behaviour. The purpose of the study was to explore coach-athlete relationships, the characteristics of Gen Z athletes that influence this relationship, and the process of building healthy coach-athlete relationships, from the perspectives of coaches.MethodsThe study used a qualitative methodology to elicit the perspectives of 11 male rugby union coaches (M ± SD age: 42.09 ± 7.56 years; with 12.83 ± 3.48 years of coaching experience), through semi-structured individual online interviews. We developed the interview script from Jowett's Coach-Athlete Relationship Questionnaire (CART-Q). The interviews were analysed using Merriam and Tisdell's six-step process.FindingsThe analysis yielded six super themes (and 17 themes). 1. Coach perspectives on coaching Gen Z players (developmental facilitators and debilitators, Covid-19's effect on development). 2. Closeness between coaches and athletes [loving and caring, getting closer, trusting, (not) respecting some players]. 3. Commitment (personally and towards the team, sacrifices). 4. Complementarity (goal setting, collectively working towards common goals). 5. Co-orientation (communicating, reciprocal relationship views). 6. Developing the coach-athlete relationship (approaches thereto, practical steps).DiscussionVarious facets of the coach-athlete relationship are interlinked and shaped by the characteristics and behaviours of this generation of athletes. Practical recommendations are offered on how to cultivate the coach-athlete relationship on emotional, cognitive, and behavioural levels.